Society of Behavior Medicine (SBM) Urges Congress to Ensure Affordable Care Act Coverage of Prostate Cancer Screening Support Services for High-Risk Men. Issue 2 (11th March 2019) - Watson, Karriem; Buscemi, Joanna; Fitzgibbon, Marian; Murray, Marcus; Murphy, Adam; Abern, Michael; Gann, Peter; Levi, Josef Ben; Stinson, James; Diefenbach, Michael; Winn, Robert A
Abstract: Prostate cancer (PCa) disproportionately affects African American men. Early detection reduces risk of mortality. The United States Preventive Services Task Force (USPSTF) issued an updated recommendation statement on serum Prostate Specific Antigen (PSA)-based screening for PCa. Specifically, in 2012, the USPSTF recommended against PSA-based screening due to risk for overdiagnosis and overtreatment. However, the updated 2018 guidelines recommend consideration of screening for certain at risk men and revised the recommendation rating from "D" to "C." This new guideline recommends providers to educate high-risk men on the benefits and harms of PSA-based PCa screening so that they can make an informed decision. The Affordable Care Act (ACA) includes provisions of service coverage for patient navigators who can help patients decide whether screening is appropriate, given potential risks and benefits, and training of health care providers in shared-decision regarding screening/treatment. These services can be utilized to support health care providers to better adhere to the new guideline. However, recommendations that are given a C rating or lower are not consistently reimbursed through many plans, including those offered through the ACA marketplace. The Society of Behavioral Medicine (SBM) supports the USPSTF guideline for the consideration of prostate cancer screening for high-risk men between the ages of 55 and 69. SBM encourages policymakers to include provisions for coverage of patient navigation services in the ACA to facilitate shared decision-making between providers and patients regarding screening. Abstract : The Society of Behavioral Medicine encourages policymakers to include provisions for coverage of patient navigation services in the Affordable Care Act (ACA) to facilitate shared-decision making between providers and patients regarding prostate cancer screening.